1998
DOI: 10.1002/(sici)1098-1136(199802)22:2<161::aid-glia7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Response of the oligodendrocyte progenitor cell population (defined by NG2 labelling) to demyelination of the adult spinal cord

Abstract: Elucidation of the response of oligodendrocyte progenitor cell populations to demyelination in the adult central nervous system (CNS) is critical to understanding why remyelination fails in multiple sclerosis. Using the anti‐NG2 monoclonal antibody to identify oligodendrocyte progenitor cells, we have documented their response to antibody‐induced demyelination in the dorsal column of the adult rat spinal cord. The number of NG2+ cells in the vicinity of demyelinated lesions increased by 72% over the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
155
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 337 publications
(173 citation statements)
references
References 38 publications
16
155
0
1
Order By: Relevance
“…This concurrent increase in NG2 cells and decrease in mature oligodendrocytes suggest a possibility that NG2 cells failed to differentiate into myelin forming cells in CPZ-exposed mice, although increased NG2 cells may be viewed as a compensatory reaction of the body to oligodendrocyte loss and demyelination as explained in previous studies. [52][53][54] In support of this view, CPZ administration significantly increased the number of BrdU C /NG2 C cells in the medial PFC, indicating that NG2 cells kept proliferating and failed to exit from cell cycle for differentiation in the CPZexposed mice. 12 More significantly, the CDK inhibitor FLA administration alleviated the CPZ-induced increase in NG2 cells and myelin breakdown in the present study.…”
Section: Cuprizone Inhibited Cell Cycle Exitmentioning
confidence: 70%
“…This concurrent increase in NG2 cells and decrease in mature oligodendrocytes suggest a possibility that NG2 cells failed to differentiate into myelin forming cells in CPZ-exposed mice, although increased NG2 cells may be viewed as a compensatory reaction of the body to oligodendrocyte loss and demyelination as explained in previous studies. [52][53][54] In support of this view, CPZ administration significantly increased the number of BrdU C /NG2 C cells in the medial PFC, indicating that NG2 cells kept proliferating and failed to exit from cell cycle for differentiation in the CPZexposed mice. 12 More significantly, the CDK inhibitor FLA administration alleviated the CPZ-induced increase in NG2 cells and myelin breakdown in the present study.…”
Section: Cuprizone Inhibited Cell Cycle Exitmentioning
confidence: 70%
“…Surviving oligodendrocytes have been shown to have limited capacity for remyelination, while oligodendrocyte precursor cells, which mature in demyelinated lesions, are the predominant cell type that will initiate central remyelination. 44 Macrophages have been observed to stimulate myelin formation in vitro, 45,46 and inflammation has been shown to be important for stimulating remyelination. 47 Macrophages have also been shown to express a variety of growth factors and cytokines, including plateletderived growth factor, epidermal growth factor, transforming growth factor beta, insulin-like growth factor, and nerve growth factor, that have been implicated in such processes as regulation of oligodendrocyte proliferation and survival, myelination, and remyelination; for a review see Diemel et al 48 Therefore, the presence of macrophages within demyelinated regions of the spinal cord might even facilitate the subsequent remyelination of demyelinated axons.…”
Section: Discussionmentioning
confidence: 99%
“…Keirstead et al (1998) suggested that after spinal cord damage the OPCs fall into two classes, a class that proliferates and a class that does not. Similarly, when EGFP was expressed via the promoter for 2,3 cyclic nucleotide 3-phosphodiesterase (CNP), two types of NG2-expressing OPCs were detected in response to spinal cord injury, one of which was bipolar, expressed EGFP, proliferated earlier and was suggested to turn into new oligodendrocytes, while the other was multipolar and did not form mature oligodendrocytes (Lytle et al, 2009).…”
Section: I F F E R E N T T Y P E S O F O P Cmentioning
confidence: 99%
“…Damage to oligodendrocyte precursors, leading to reduced myelination, contributes to mental and physical impairment in periventricular leukomalacia (pre-or perinatal white matter injury leading to cerebral palsy; Volpe, 2001). Adult OPCs may form new myelinating oligodendrocytes in multiple sclerosis, and in brain or spinal cord injury (Levine, 1994;Gensert and Goldman, 1997;Keirstead et al, 1998;McTigue et al, 2001;Levine et al, 2001;Horner et al, 2002), and OPC transplants could serve as a basis for therapeutic remyelination (Windrem et al, 2008;Moreno-Manzano et al, 2009). This article will focus on the electrical signalling properties of OPCs which, as we will describe below, may play a crucial role in their development and their myelination of axons.…”
Section: Introductionmentioning
confidence: 99%